Reclaiming identity : realist theory and the predicament of postmodernism - Moya, Paula M. L.; Hames-Garcia, Michael Roy (University of California Press, 2000)
This collection of ten essays argues that identity is not just socially constructed but has real epistemic and political consequences. They examine the way theory, politics and activism clash with or complement each other, providing an alternative to the widely influential understandings of identity.